A Maternal Gene Regulator CPEB2 Is Involved in Mating-Induced Egg Maturation in the Cnaphalocrocis medinalis - Yi Duan; Yueran Xiao; Guo Cai; Kepeng Wang; Chenfan Zhao; Pengcheng Liu (Insects, 2025)
Cytoplasmic polyadenylation element-binding proteins (CPEBs) are critical regulators of maternal mRNA translation during oogenesis, yet their roles in insect reproduction remain underexplored. Here, we characterized CmCPEB2, a CPEB homolog in the rice leaf roller Cnaphalocrocis medinalis, a destructive lepidopteran pest insect, and elucidated its role in mating-induced oviposition. The CmCPEB2 protein harbored conserved RNA recognition motifs and a ZZ-type zinc finger domain and was phylogenetically clustered with lepidopteran orthologs. Spatiotemporal expression profiling revealed CmCPEB2 was predominantly expressed in ovaries post-mating, peaking at 12 h with a 6.75-fold increase in transcript levels. Liposome-mediated RNA interference targeting CmCPEB2 resulted in a 52% reduction in transcript abundance, leading to significant defects in ovarian maturation, diminished vitellogenin deposition, and a 36.7% decline in fecundity. The transcriptomic analysis of RNAi-treated ovaries identified 512 differentially expressed genes, with downregulated genes enriched in chorion formation and epithelial cell development. Tissue culture-based hormonal assays demonstrated the juvenile hormone-dependent regulation of CmCPEB2, as JH treatment induced its transcription, while knockdown of the JH-responsive transcription factor CmKr-h1 in the moths suppressed CmCPEB2 expression post-mating. These findings established CmCPEB2 as a juvenile hormone-dependent regulator of mating-induced oviposition that orchestrates vitellogenesis through yolk protein synthesis and ovarian deposition and choriogenesis via transcriptional control of chorion-related genes. This study provides novel evidence of CPEB2-mediated reproductive regulation in Lepidoptera, highlighting its dual role in nutrient allocation and structural eggshell formation during insect oogenesis and oviposition.